2020
DOI: 10.1159/000508477
|View full text |Cite
|
Sign up to set email alerts
|

TMEM63C, a Potential Novel Target for Albuminuria Development, Is Regulated by MicroRNA-564 and Transforming Growth Factor beta in Human Renal Cells

Abstract: <b><i>Introduction:</i></b> Transmembrane protein (TMEM) 63C is a member of the TMEM gene family and was recently linked to glomerular filtration barrier function and albuminuria. Its molecular function and expression regulation are largely unknown. <b><i>Objective:</i></b> In this study, we set out to characterize the regulating impact of microRNAs (miRNAs) such as miRNA-564 (miR-564) on TMEM63C expression in renal cells. Also, we examined the influence of trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Although the speci c functions of TMEM family proteins are still poorly characterized, new ndings have highlighted the importance of the TMEM family as prognostic markers for various diseases [33][34][35] . Among TMEM family proteins, TMEM45A has been reported to be correlated with epidermal keratinization through the Golgi network in both in vivo and in vitro models [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the speci c functions of TMEM family proteins are still poorly characterized, new ndings have highlighted the importance of the TMEM family as prognostic markers for various diseases [33][34][35] . Among TMEM family proteins, TMEM45A has been reported to be correlated with epidermal keratinization through the Golgi network in both in vivo and in vitro models [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown significantly reduced expression of TMEM136 in iris and ciliary body tissues in PEX patients [ 3 , 9 , 55 , 56 ]. TMEM63C ( locus 14q24.3 ) encodes transmembrane protein 63C, which enables calcium-activated cation channel activity and is involved in cation transport [ 57 , 58 ]. Calcium participates in regulating voltage-gated sodium, calcium, and potassium channels [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on age-related macular degeneration, a suggestive association signal in TMEM63C was found, but its role in AMD pathogenesis is unknown [ 61 ]. Additionally, TMEM63C is considered a biomarker of focal segmental glomerulosclerosis (FSGS) [ 57 , 62 ]. FSGS shows the obliteration or collapse of glomerular capillary loops via increased ECM [ 63 ].…”
Section: Discussionmentioning
confidence: 99%